2019
DOI: 10.4067/s0718-50732019000200181
|View full text |Cite
|
Sign up to set email alerts
|

Optimización metaheurística de conjuntos estructurales de hormigón armado

Abstract: This paper presents the economic structural optimization of the Casa Síndico project using an algorithm programmed through the CSi API functions SAP2000v19-MATLAB R2015a, applying metaheuristic techniques: Genetic Algorithms (GA) and Particle Swarm Optimization (PSO), in addition to hybridization between them. The results show that PSO has a better performance than GA for this type of optimization, although both, working with their simple methodologies, are not completely efficient, which is verified when crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
(2 reference statements)
0
6
0
Order By: Relevance
“…The practical objective function is the total direct cost of the structure (beams, columns and foundations), taking into account the formwork, the elaboration and placement of steel (longitudinal and stirrups) and concrete, and the cost of excavation and refill in foundations [4,5]. For more information, check the previous references.…”
Section: Objective Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The practical objective function is the total direct cost of the structure (beams, columns and foundations), taking into account the formwork, the elaboration and placement of steel (longitudinal and stirrups) and concrete, and the cost of excavation and refill in foundations [4,5]. For more information, check the previous references.…”
Section: Objective Functionmentioning
confidence: 99%
“…The results of the real case study optimization process (with soil 1) using BBO with its tuned parameters is compared to simple GA and simple PSO, just as had previously been used in [4]. In Figure 9 it can be seen the superiority of BBO, and the dynamism mentioned above because this method constantly improves its solutions.…”
Section: Application To the Real Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An essential part of the mathematical formulation of the whole optimization process are the constraints imposed to the problem, consistently with the minimum cost requirement. It is known that design variables depend on constraints, which limit their free circulation in the optimization process (Negrin,. 2014).…”
Section: Identification Of the Constraintsmentioning
confidence: 99%
“…Furthermore, it is essential to understand the structural optimization as the result of optimizing the whole set, since it has been demonstrated that the optimization of individual elements omits a key aspect of the concept of structure, which is the influence of each individual element on the whole, where load distributions are strongly influenced by this aspect (Negrin, 2014) (Negrin, 2016) (Negrin, 2019). obtaining the minimum structure weight, where the process starts with small sections and progressively increases the dimensions, until the strength and stiffness criteria are met, although poor results are obtained, such as beams with square sections (Mejía and Orozco, 2019).…”
Section: Introductionmentioning
confidence: 99%